THE IMPACT OF GLOBALIZATION ON CURRICULUM: CHALLENGES AND OPPORTUNITIES IN A CONNECTED WORLD - Sana Niaz; Atif Saeed; Naveen Mazhar (International Journal of Contemporary Issues in Social Sciences, 2024)
The main research purpose of the paper is to investigate the intricate interrelations between globalization and curricular development. Hence, the paper provides the possibility to look at the problems and opportunities, brought about by an increasingly interconnected and technologically advanced world. Taking a look at different educational systems and seeing how they have responded to globalization is the basis of this study which acknowledges the potential of innovative approaches and best practices that can be used to develop curricula that are efficient in making students ready for the complexities of the globally-oriented world. The use of a mixed method approach comprised of qualitative interviews, surveys and comparison analysis would provide the research project with an in-depth view of the educational shaping forces of the global society. These insights will help educators, policymakers and curriculum developers improve their understanding and respond to the newly emerging challenges in the international education trends. The result of this study will hopefully inform educators, policy makers and curriculum developers about the current unique situations as well as futuristic inclinations of globalized curriculum in the global education system which is directed to improving and strengthening the system.